Kidney and inferior vena cava abnormalities with leg thromboses (KILT) syndrome: A case report and literature review. Issue 5 (10th April 2019) - Rughani, Prita; Yeung, Frances; Halgren, Camilla Raya; Cada, Michaela; Schwartz, Sarah
Abstract: Venous thromboembolism (VTE) is now increasingly recognized within paediatrics. A Canadian VTE registry has estimated the incidence as 0.7 to 1.0 per 100, 000 population, with a peak in infancy and adolescence. Congenital inferior vena cava agenesis (IVCA) is an important risk factor that may be unfamiliar to paediatricians. Several case reports have since described an association between IVCA, VTE, and renal hypoplasia, which has been referred to as KILT syndrome (Kidney and IVC abnormalities with Leg Thromboses). We describe the first reported paediatric case of KILT syndrome in Canada. In any young patient presenting with a spontaneous DVT, particularly, if it is bilateral in nature with no co-existing risk factors for thrombus formation, we recommend investigating for the possibility of an underlying congenital vena cava anomaly. The use of prolonged anticoagulant therapy is supported by the inherent life-long risk of recurrent thrombosis associated with IVC anomalies.